Holding the mirror up to converted languages: Two grammars, one lexicon. (April 2021) - Meakins, Felicity; Pensalfini, Rob
Aims and objectives/purpose/research questions: This article describes an unusual result of language contact occurring in North-Central Australia, where extensive long-term contact between speakers of the genetically unrelated Jingulu and Mudburra has resulted in a high degree of lexical borrowing, with little if any change to syntactic or morphological structure in either language. What is particularly unusual about this borrowing is that it is bidirectional, with almost equal numbers of words being borrowed from Jingulu into Mudburra as vice versa. This situation mirrors that of converted languages, where two varieties have come to share a grammar through contact, but retain separate lexicons. Design/methodology/approach: We use a comparative database to establish the direction of noun borrowings between these languages. Data and analysis: The comparative database consists of 871 nouns shared by Jingulu and Mudburra and also includes 571 corresponding nouns from a number of geographically and phylogenetically neighbouring languages: Wambaya, Gurindji, Jaminjung, Jaru, Warlmanpa and Warumungu. Findings/conclusions: We show that for nouns alone, Mudburra and Jingulu share 65% of their forms. What makes the Jingulu-Mudburra situation even more unusual is the relatively balanced bidirectional nature of borrowings, with 32% of shared nouns originating in Mudburra and 24.5% from Jingulu (for the remaining 43.5%, direction of borrowing could not be determined). Originality: We suggest that that this situation of bidirectional borrowing represents a hitherto unreported type of language hybridisation scenario, which we dub 'lexical convergence'. Significance/implications: We claim that this unusual situation is the result of long-term cohabitation of the two groups, a shared cultural life and relative socio-political equality between the two groups. We venture that these may be requisite to the sort of extensive bidirectional borrowing and maintenance of individual grammatical systems found in lexical convergence more generally.